Scale Up Sourcebook - and Cooley, Larry; Howard, Julie (Purdue University, 2019)
The Scale Up Sourcebook is informed and inspired by the September 2018 conference, Innovations in Agriculture: Scaling Up to Reach Millions, organized by Purdue University, in partnership with the African Development Bank. The Sourcebook consolidates, extends, and disseminates some of the scaling insights presented at the Purdue conference. It is intended as an easy-to-use guidebook targeted to a broad and diverse audience of stakeholders associated with scaling agricultural technologies and innovations to meet the needs of the world’s poor. The Sourcebook has nine chapters: designing with scale in mind; assessing scalability; using commercial markets to drive scaling; financing the transition to scale; creating an enabling environment for scale; tailoring metrics, monitoring, and evaluation to support sustainable outcomes at scale; and the critical role of intermediary and donor organizations. The Sourcebook provides guidance, tips, and examples, along with links and references to additional resources on scale up.